Dermatitis herpetiformis presenting as intertriginous dermatitis - Pavlović, Miloš (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
A 54-year old man with atypical dermatitis herpetiformis Duhring lasting aboutthree years is reported. The lesions were located exclusively in the pubic area, groins, inner thighs and perianal regions. Routine histopathology and the direct as well as the indirect immunofluorescence supported the diagnosis. Application of a gluten-free diet and dapsone alleviated the symptoms.
Keywords: Biopsija; Biopsy; Dermatitis Herpetiformis; Dermatitis herpetiformni; Diagnosis; Fluorescent Antibody Technique, Direct; Fluoresenčno protitelo, tehnika direktna; Iga; Middle Age; Pathology; Srednja leta; Therapy